Excitation Analysis of Transverse Electric Mode Rectangular Waveguide - M. Reza Hidayat; Mohamad Hamzah Zamzam; Salita Ulitia Prini (Jurnal Elektronika dan Telekomunikasi, 2020)
A waveguide is a transmission medium in the form of a pipe and is made from a single conductor. A waveguide has the function of delivering electromagnetic waves with a frequency of 300 MHz - 300 GHz and is able to direct the waves in a particular direction. In its development, a waveguide can be used as a filter. A filter consists of several circuits designed to pass signals that are generated at a specific frequency and attenuate undesired signals. One type of filter that can pass a signal in a particular frequency range and block signals that are not included in that frequency range is a bandpass filter. In this article, we study a rationing analysis on rectangular waveguide using TEmn mode followed by an implementation of a bandpass filter in the frequency range of 3.3-3.5 GHz for S-Band Wireless Broadband and Fixed Satellite. The observation process is done by shifting the position of the connector (power supply) as much as five times the shift to get the results as desired. Based on the analysis of the simulation process using Ansoft HFSS software, it is observed that the optimized results of the rectangular waveguide mode TE10 were obtained at a distance between connectors of 30 mm with a cut-off frequency of 3.3 GHz, the value of the return loss parameter of -34.442 dB and an insertion loss of -0.039 dB. Whereas, the optimized TE20 mode can be obtained at a distance of 70 mm between connectors, with a cut-off frequency of 3.5 GHz, the value of the return loss parameter of -28.718 dB and an insertion loss of -0.045. The measurement of TE10 mode in our Vector Network Analyzer (VNA) shows a cut-off frequency of 3.2 GHz, with a value of the return loss of -18.73 dB and an insertion loss of -2.70 dB. Meanwhile, a measurement of TE20 mode results in a cut-off frequency of 3.2 GHz, with a value of the return loss of -5.89 dB and an insertion loss of -4.31 dB.